2008
DOI: 10.1016/j.humpath.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of Helicobacter DNA in benign and malignant liver tissues from Baltimore, United States

Abstract: Helicobacter DNA has been reported in hepatocellular carcinoma tissues in several studies from varying geographical locations, raising the possibility that helicobacter infection may contribute to the pathogenesis of hepatocellular carcinoma. Other known risk factors for hepatocellular carcinoma show significant geographical variability, but whether the same holds for helicobacter is unknown. We studied the prevalence of Helicobacter DNA in a United States cohort of HCC, where the prevalence of helicobacter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Increasing evidence suggests that H. pylori may be a risk factor for the development of cirrhosis and HCC in patients with CHC [ 8 10 ]; however, some researchers have suggested that H. pylori might not contribute to the mechanism of HCV-related HCC [ 11 , 12 ]. The relationship between H. pylori and CHC remains controversial, and it is unclear whether H. pylori is associated with CHC and the progression of HCV-related cirrhosis and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that H. pylori may be a risk factor for the development of cirrhosis and HCC in patients with CHC [ 8 10 ]; however, some researchers have suggested that H. pylori might not contribute to the mechanism of HCV-related HCC [ 11 , 12 ]. The relationship between H. pylori and CHC remains controversial, and it is unclear whether H. pylori is associated with CHC and the progression of HCV-related cirrhosis and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Another important complication of cirrhosis is hepatocellular carcinoma (HCC), that is mostly associated with the exposure to chronic liver infections (hepatitis B and C virus), Aspergillus mycotoxin, aflatoxin‐B1, and alcohol, but in which other unrecognized risk factors may potentially be involved. While some experimental studies have suggested that H. pylori may play a role in the developing of HCC [39], a recent study showed a low frequency of H. pylori DNA in benign and malignant liver tissues, concluding that H. pylori infection is unlikely to be etiologically associated with HCC [40], while another study described the presence of H. pylori DNA and vac A gene‐specific markers in HCC and cholangiocarcinoma specimens [41].…”
Section: Extragastric Manifestations Of H Pylori Infectionmentioning
confidence: 99%
“…Gastric Helicobacter species, including NHPH, are associated with gastritis [80,81], gastric ulceration, gastric adenocarcinoma, and gastric mucosa‐associated lymphoma [82]. Several EHS have been associated with disease ranging from subclinical inflammation to cancer in the intestinal tract and hepatobiliary system [40,83–87] and an increased risk of biliary lithiasis [88,89].…”
Section: Other Helicobacter Speciesmentioning
confidence: 99%
“…Any association between such prevalent diseases is of obvious pathophysiological and public health interest. Recently, as well a higher and a lower prevalence of HP DNA in liver tissue with HCC and chronic liver disease is reported and the findings are of unclear significance [13][14][15][16][17][18][19][20] . A single study from Ethiopia describes a higher prevalence of HP antigen in faeces in HCC patients compared with controls 21 .…”
Section: Introductionmentioning
confidence: 99%